A Study of Hypertensive Retinopathy Changes for Stroke Prediction - Ng, Guan Shen (Universiti Teknologi PETRONAS, 2017)
Hypertensive retinopathy is an ailment that is highly connected to hypertension which help in stroke prediction. The presence of hypertensive retinopathy is diagnosed through image processing on the fundus image to identify the possible microvascular retinal abnormalities signs that lead to hypertension. Arterio-Venous Ratio (AVR) value is one of the main indicator of hypertensive retinopathy, useful for grading severity of hypertensive retinopathy and for prediction of risk of stroke. Image preprocessing were performed in this work to extract vessels in fundus image. In this thesis, fundus images were acquired from VICAVR and DRIVE databases.